Employee Performance 2.0: Antecedents and Consequences of Gen Z Employees Performance - Wulur, Lies; Mandagi, Deske W. (SEIKO : Journal of Management & Business, 2023)
Generation Z (Gen Z) employee performance has become a major topic of focus for firms seeing to optimize their workforce and enhance overall efficiency. However, the dynamic nature of Gen Z employee performance is largely unknown, leaving a notable research gap. This study aims to address this gap by conducting a systematic literature review on the antecedents and consequences of Gen Z employee performance. A comprehensive selection and evaluations of relevant literature was conducted utilizing the Scopus and Web of Science (WOS) databases. A total of 45 research studies were carefully chosen using keywords such as "Gen Z employee," "factors influencing Gen Z employee performance," and "outcomes of Gen Z employee performance." The findings of the systematic literature review shed light on the multifaceted factors influencing Gen Z employee performance. The antecedents of Gen Z employee performance were explored, revealing crucial elements such as technological proficiency, work-life balance, inclusive work environment, career advancement as influential contributors to their performance outcomes. Additionally, the consequences of Gen Z employee performance were examined, uncovering potential impacts on individual creativity and innovation, job satisfaction, and overall business performance. Furthermore, Gen Z employee performance affects organizational outcome such as performance, culture, and employee rentention. The research findings contribute to a better understanding of how Gen Z employees' unique characteristics, preferences, and behaviors shape their performance, allowing for the development of tailored approaches to improve their productivity and well-being at work. Keywords- Employee performance; Gen Z, employee performance outcomes, employee performance antacedents